OCCURENCE OF UNDIAGNOSED ORTHODONTIC ANOMALIES IN CHILDREN AT ELEMENTARY SCHOOLS IN OLOMOUC REGION - P Kamínková; P Dírer; M Kamínek (Czech Dental Chamber, 2021)
Introduction, aim: Within regular preventive dental check ups, dentists are obligated to asses in oral cavity not only hard and soft tissues, but also the intercuspidation and relation of dental arches. Reality, that some anomalies are indicated for early (interceptive) treatment, underlines importance of orthodontic assessment in children with mixed and young permanent dentition. The aim of this paper was to find out with noninvasive clinical assessement the occurence of children aged 6-13.9 years with orthodontic anomalies at elementary schools in Olomouc region, that so far were not in orthodontic dispensarization or treatment. Material and methods: Intraoral assessment of potential orthodontic anomalies was performed in 312 pupils of elementary schools in Olomouc region aged 6 to 13.9 years (134 boys and 178 girls). The pupils were divided into categories according sex and age (6-7.9 years, 8-9.9 years, 10-11.9 years and 12-13.9 years). The occlusion in maximal intercuspidation, Angle class, overjet and overbite were assessed in every child. If orthodontic anomaly was diagnosed and simultaneously this anomaly has not been in treatment yet, the child received request form for further examination in Orthodontic Department of Clinic of Dentistry in Olomouc. Results: Total 33 children had an undiagnosed or untreated orthodontic anomaly, that made 10.58% of all assessed children. The anomalies were more frequent in girls (11.24%) than in boys (9.70%). In younger age categories (6-7.9 years and 8-9.9 years) the frequency of those anomalies was approximately 6%, in older age categories (10-11.9 years a 12-13.9 years) the frequency was up to 15%. The most common diagnosed untreated anomaly was negative overjet, followed by increased overjet and lateral crossbite. Conclusions: The occurence of untreated orthodontic anomalies in observed children was relatively high. That can be explained with only three reasons: Either the child did not regularly visit his/her dentist, the doctor failed to diagnose anomaly within regular check up, or the parents were not interested in treatment after the doctor's recommendation.